2016
DOI: 10.18632/oncotarget.8978
|View full text |Cite
|
Sign up to set email alerts
|

Sorafenib-resistant hepatocellular carcinoma stratified by phosphorylated ERK activates PD-1 immune checkpoint

Abstract: Sorafenib is a multikinase inhibitor approved as the first line treatment for late stage hepatocellular carcinoma (HCC). Due to its significant variation in clinical benefits among patients, defining prognostic biomarkers for sorafenib sensitivity in HCC would allow targeted treatment. Phosphorylated extracellular signaling-regulated kinase (pERK) was proposed to predict the response to sorafenib in HCC, but clinical supports are mixed or even contradictory. Here we found that pERK expression levels are variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 30 publications
3
26
0
Order By: Relevance
“…This is consistent with the recent findings of the Zhang et al. in vitro study and our previous study .To explore the underlying mechanisms, we carried out RNA‐seq to discover gene expression changes with Sorafenib treatment in HCC cell lines that differentially express pERK (HepG2 and HCC‐0010). We found out that there were significantly more genes whose expression levels changed over fourfold after Sorafenib treatment in the HepG2 cells relative to HCC‐0010 cells (Table ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This is consistent with the recent findings of the Zhang et al. in vitro study and our previous study .To explore the underlying mechanisms, we carried out RNA‐seq to discover gene expression changes with Sorafenib treatment in HCC cell lines that differentially express pERK (HepG2 and HCC‐0010). We found out that there were significantly more genes whose expression levels changed over fourfold after Sorafenib treatment in the HepG2 cells relative to HCC‐0010 cells (Table ).…”
Section: Discussionsupporting
confidence: 87%
“…To examine the efficacy of Sorafenib on individual tumors, we generated patient‐derived xenografts using surgically removed HCC tissue. Unfortunately, we could only recruit three pairs of patient‐derived primary HCC xenografts at that time, and our results may have suffered from selection bias .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In HCC, SR may be inherent wherein the cancer cells typically express less phospho‐ERK and phosphatase and tensin homolog but more phospho‐AKT . More commonly, however, resistance is acquired where the cells augment critical cell‐autonomous survival mechanisms by, for example, increasing expression of EGFR or exploiting noncancerous cells of the tumor microenvironment, to sustain a drug‐resistant tumor‐permissive niche.…”
Section: Discussionmentioning
confidence: 99%
“…By inducing sorafenib‐resistant HCC cell lines, they found that highly upregulated DNMT1 was positively correlated with PD‐L1 overexpression in sorafenib‐resistant HCC cells. Chen et al revealed that pERK‐negative, PD‐1‐positive patients have poorer OS and DFS than pERK‐positive, PD‐1‐negative patients. Accordingly, patients with pERK‐positive, PD‐1‐positive HCC, a minor population (less than 10%) but the one with the worst postoperative recurrence, might benefit the most from combination therapy with anti‐PD‐1 antibody and sorafenib.…”
Section: Pd‐l1 Expression In Acquired Resistance To Sorafenibmentioning
confidence: 99%